Prospective Evaluation of Surgical Wound Dressings and the Incidence of Surgical Site Infections in Dogs Undergoing a Tibial Plateau Levelling Osteotomy - Giannetto, Jessica J.; Aktay, Sevima A. (Veterinary and Comparative Orthopaedics and Traumatology, 2019)
Objective The main aim of this study was to evaluate the efficacy of a topical 2-octyl cyanoacrylate (2OC) tissue adhesive and an adhesive barrier dressing (BD) in minimizing the incidence of surgical site infections (SSI) in dogs undergoing a tibial plateau levelling osteotomy (TPLO).Materials and Methods In a prospective clinical study, 437 client-owned dogs undergoing a TPLO as treatment for cranial cruciate ligament disease with or without concurrent patellar luxations from July 2015 to September 2016 were included. In each dog, the type of postoperative wound dressing was randomly selected as either no dressing (ND), a 2OC tissue adhesive or an adhesive BD. Direct examination by a veterinarian was performed at 14, 30, 60 and 90 days postoperatively. If dogs did not return for direct examination, owners were contacted with a questionnaire for the final follow-up of at least 90 days.Results The overall rate of SSI was 2.3% (10/437). Methicillin-resistant Staphylococcus pseudintermedius was the most common bacteria isolated in 9/10 cases. Infection was confirmed in 2.76% (4/145) of dogs with ND, 2.01% (3/149) of dogs with 2OC and 2.10% (3/143) of dogs with BD. Of the dogs that developed an SSI, type of dressing was not a significant risk factor (p = 0.5305) for infection. Increasing body weight was the only significant risk factor that increased the risk of overall infection (odds ratio = 1.03 [95% confidence interval: 1.02–1.05]).Clinical Significance In dogs undergoing a TPLO, there may be no clear benefit in the usage of postoperative wound dressings for the prevention of SSI. Increasing body weight was the only significant factor associated with the development of an SSI.
Keywords: surgical site infection; tibial plateau levelling osteotomy; wound dressings; dogs